Quorum-Sensing-Regulated Bactobolin Production by Burkholderia thailandensis E264 - Seyedsayamdost, Mohammad R. (American Chemical Society, 2010)
[Image: see text] Bacterial acyl-homoserine lactones upregulated an uncharacterized gene cluster (bta) in Burkholderia thailandensis E264 to produce an uncharacterized polar antibiotic. The antibiotic is identified as a mixture of four bactobolins. Annotation of the bta cluster allows us to propose a biosynthetic scheme for bactobolin and reveals unusual enzymatic reactions for further study.